MEASURING AND ANALYZING THE IMPACT OF THE ECONOMIC COSTS OF TRAFFIC ACCIDENTS ON ECONOMIC GROWTH IN IRAQ FOR THE PERIOD 2004-2021 (World Bulletin of Management and Law, 2023)
Traffic accidents constitute a negative and serious challenge to society, and are considered a factor that has an impact on the loss of material and human energies by increasing death rates or increasing the number of injured as a result of them. It is up to the individual to determine his different abilities and the accompanying economic, social and psychological crises and problems that are extremely complex. This research aims to analyze and measure the impact of the economic costs of traffic accidents on economic growth in Iraq and the goals of economic development using the Eviews 12 program. With its counterpart in other countries. The research also found that there is an adverse and significant effect in the short and long term of the costs of deaths and injuries on the gross domestic product according to the US costs as a result of traffic accidents, that is, when an increase (the cost of deaths X1, the cost of injuries X2) leads to a decrease in GDP Y And the presence of an adverse and significant effect in the short and long term for the costs of deaths and injuries according to the German costs as a result of traffic accidents, that is, when increasing (the cost of deaths x1 and the cost of injuries X2) leads to a decrease in the gross domestic product Y. The research also found that there is a long-term equilibrium relationship between the economic costs of traffic accidents and the gross domestic product, according to the results of joint integration. As well as the absence of the problem of autocorrelation, and the absence of the problem of homogeneity of variance at the level of significance 5%. The research recommended some proposals, the most important of which is the application of the traffic system and the penalties stipulated in the system for traffic violations with full firmness and responsibility by the designated authorities. And the use of traffic awareness throughout the year in all media and in schools and the introduction of the traffic system within the school curricula, with a focus on explaining the economic and social impacts and losses of traffic accidents.